Abrupt Change of the Generalized Complementary Relationship of Evaporation Over Irrigated Double Cropping North China Plain With East Asian Monsoon. Issue 4 (4th April 2023) - Han, Songjun; Zhao, Yujie; Zhang, Baozhong; Wang, Yaqi; Lei, Huimin; Zhang, Xiaolong; Zhao, Fenghua
Abstract: The generalized complementary relationship (CR) of evaporation was investigated in the irrigated winter wheat/summer maize double‐cropping sites in North China Plain (NCP), a region influenced by the East Asian dry winter and wet summer monsoon. Different generalized CRs exist in the winter wheat (dry) and summer maize (wet) seasons with abrupt changes in June and October. The seasonal abrupt change in the CR is attributed to the sudden reversed water vapor transport with the winter and summer monsoon and the wheat/maize rotation with irrigation in the winter wheat season. The separation and abrupt change in the complementary behavior require that two‐stage phased parameters corresponding to the wheat (dry) and maize (wet) seasons should be adopted by the generalized complementary functions for operational evaporation estimation in the irrigated double cropping NCP. Plain Language Summary: The irrigated double cropping North China Plain (NCP) is characterized with rapid winter wheat/summer maize rotation on the land surface and sudden reversed water vapor transport in the upper‐air with East Asian monsoon, coincidentally in June and October. There are corresponding abrupt changes of the complementary relationship, a theory relating changes in landscape evaporation and atmospheric evaporation demand. It reveals the impacts of the processes related to large‐scale changes in atmospheric circulations on the complementary behavior and the requirement of different parameters during the two stages for operational evaporation estimation using the complementary principle in the irrigated double cropping NCP. Key Points: Different generalized complementary relationships (CRs) exist in winter wheat and summer maize seasons with an abrupt change Abrupt change of the CR is mainly attributed to upper‐air circulations with East Asian monsoon Wheat season irrigation contributes to the abrupt change via interrupting the connection between land surface and atmosphere